Diagnosing the rapid intensification of Hurricane Patricia (2015) from observations - Martinez, Jonathan, author; Bell, Michael M., author (Colorado State University. Libraries, 2017)
Hurricane Patricia (2015) made history as the strongest tropical cyclone in the western hemisphere with a peak intensity of 185 knots. Patricia set various records with the most noteworthy being its unprecedented rapid intensification of 105 knots in 24 hours. Although this dramatic intensification was not well captured by forecast models, high-resolution observations gathered by aircraft penetrating the eye of Patricia allow for a thorough investigation of the mechanisms that may have contributed to its evolution. Preliminary results suggest that Patricia’s ability to efficiently concentrate convection in a remarkably narrow annulus surrounding the eye led to its rapid intensification.
183 - Jon Martinez
Keywords: tropical cyclones